Genetic structure and phylogeny of Italian and Czech populations of the cucurbit powdery mildew fungus Golovinomyces orontii inferred by multilocus sequence typing. (30th November 2015) - Pirondi, A.; Kitner, M.; Iotti, M.; Sedláková, B.; Lebeda, A.; Collina, M.
Abstract : Cucurbit powdery mildew caused by Golovinomyces orontii is a serious disease that affects cucurbit crops in temperate areas. In northern Italy, the species is responsible for the early infections at the beginning of the growing season. However, chasmothecia have never been recorded in Italy and the impact of either asexual or sexual reproduction of G. orontii remains to be determined. To investigate and compare the genetic structure of Italian populations with those from the Czech Republic, where chasmothecia are sporadically recorded, seven housekeeping gene fragments ( tef‐1α, csI, ITS, H3, tub2, IGS and mtLSU ) were amplified and used in a multilocus sequence typing (MLST) approach. The four‐gamete test was performed to detect recombination between and within populations. Phylogeny was inferred using both Bayesian and minimum evolution analyses. Results from MLST revealed the presence of 141 single nucleotide polymorphisms and the existence of 13 different haplotypes. Phylogenetic analysis revealed the existence of two main distinct phylogenetic groups that were also highly genetically different, confirming that G. orontii is a species complex. Recombination was detected within both the phylogenetic groups and the geographical populations, indicating that sexual reproduction could have occurred. However, considering the lower haplotype diversity and the high frequency of ST3 (17 isolates) and ST7 (eight isolates) haplotypes, the Italian population could be predominantly clonal, while sexual reproduction may occasionally occur due to the introduction of genotypes similar to those from the Czech Republic.